Management practice and soil properties affect plant productivity and root biomass in endophyte-symbiotic and endophyte-free meadow fescue grasses - Keronen Sanna; Helander Marjo; Saikkonen Kari; Fuchs Benjamin (John Wiley & Sons, Inc., 2025)
Introduction
Pesticides are increasingly used in intensely managed agro-environments, with an increasingly acknowledged impact on crop production, root establishment and plant resilience. At the same time management practices are intensified with the goal to maximize productivity.
Materials and Methods
In a greenhouse, we studied the effects of three mowing regimes (uncut, and cutting 5 or 15 cm) employed three times during the season on root and shoot biomass and chlorophyll content of the cool-season grass Festuca pratensis (meadow fescue) growing in soil with a history of glyphosate-based herbicide (GBH) use, the corresponding control soil, and sterilized control soil. Half of the plants hosted a systemic and vertically transmitted fungal endophyte, Epichloë uncinata, which is known to promote host grass growth.
Results
Endophyte symbiosis did not affect any tested plant parameters. Cutting the plants to 5 cm decreased both root and cumulative shoot biomass. Herbicide soil history, together with intense cutting (5 cm), caused a decrease in shoot biomass and lowered the chlorophyll content. Surprisingly, soil sterilization boosted shoot biomass and chlorophyll concentrations during less intense cutting (15 cm) and noncutting when compared to the control soil. Root biomass reduced in uncut plants when growing in soil with a history of glyphosate use.
Conclusion
Our results indicate that GBH residues in the soil can diminish shoot biomass when grass is frequently cut. Decreased root biomass caused by soil glyphosate history goes together with a reduction of carbon allocation belowground, which decreases grassland resilience to climate warming, increasingly occurring droughts and extreme weather events